PENGARUH KEBIJAKAN UTANG, KEPEMILIKAN INSTITUSIONAL DAN KOMPENSASI RUGI FISKAL TERHADAP AGRESIVITAS PAJAK - Nandaliny, Dea Talitha; Angraini, Dila (IJMA (Indonesian Journal of Management and Accounting), 2024)
Tax Agressiveness is tax planning bt This study aims to determine the effect of Tax Saving, Institutional Ownership and Tax Loss Compensation on Tax Agressiveness. The method used is a quantitave methid by taking financial statement data on energy companies sector listed on the Indonesian Stock Exchange in 2018-2022. The sampling technique in this study used the purposive sampling technique, with a research sample of 66 samples. Data analysis was performed using Eviews 9. This study used descriptive analysis, panel data method, classical assumption test, determinant coefficient test, simultaneous test (F test) and partial test (T test). The result of the study simultaneously show that Tax Saving, Institutional Ownership and Tax Loss Compensastion has a effect on Tax Agressiveness. Partially, Tax Saving has no effect on Tax Agressiveness, Institutional Ownership has no effect on Tax Agressiveness, and Tax Loss Compensation has no effect on Tax Aggresiveness. Based on the determination test with an R-square, the variable is able to be explained by an independent variable of 35,3% while the remaining 64,7% is influenced by other independent variables that were not studied in this study.